On the Legal Status of Human Cerebral Organoids: Lessons from Animal Law - Jowitt, Joshua (Cambridge quarterly of healthcare ethics, 2023)
This paper will ask whether the legal status presently afforded to nonhuman animals ought to influence regulatory debates concerning human cerebral organoids. The New York Courts recently refused to grant a writ of habeas corpus to Happy the Elephant as she was property rather than a legal person while at the same time accepting that she is a moral patient deserving of rights protection. An undesirable situation has therefore arisen in which the law holds a being with moral status to be incapable of benefitting from legal redress due to their legal status as property.The author argues that this is something that we ought to avoid when designing the regulatory framework which will govern the use of human cerebral organoids. Yet, a difference exists in that, whereas the judges already accept Happy is a moral patient, there is presently no consensus around the moral status of organoids. This paper will consider whether human cerebral organoids have passed the moral threshold of sentience. If they have, or are close to doing so, regulators ought to consider their legal status in advance so as to ensure that adequate limitations are placed on this usage so as to avoid unethical practices.